Changes in Climate Vulnerability and Projected Water Stress of The Gambia's Food Supply Between 1988 and 2018: Trading With Trade-Offs - Hadida, Genevieve; Ali, Zakari; Kastner, Thomas; Carr, Tony W.; Prentice, Andrew M.; Green, Rosemary; Scheelbeek, Pauline (Frontiers in Public Health, 2022)
Background The coexistence of under- and overnutrition is of increasing public health concern in The Gambia. Fruits, vegetables and pulses are essential to healthy and sustainable diets, preventing micronutrient deficiencies and non-communicable diseases, while cereals significantly contribute to energy intake. However, environmental changes are predicted to intensify, reducing future yields of these crops if agricultural productivity and resilience are not improved. The Gambia is highly climate-vulnerable and import-dependent, but the extent of its reliance on other climate-vulnerable countries for its supply of nutritionally important crops is currently unknown. Methods We used United Nations Food and Agriculture Organization data, with novel origin-tracing algorithms applied, to analyse The Gambia's supply of cereals, fruits, vegetables and pulses between 1988 and 2018. The climate vulnerability of countries was assessed using Notre Dame Global Adaptation Initiative (ND-GAIN) index scores, and projected water stress (2040) assessed using World Resources Institute (WRI) scores. Multilevel generalized linear mixed-effects models were used to identify changes in the overall climate vulnerability and projected water stress of supply. Results Between 1988 and 2018, The Gambia's supply of cereals, fruits, vegetables and pulses diversified, with the proportion domestically produced falling (Cereals: 61.4%–27.7%; Fruits: 93.0%–55.7%; Vegetables: 24.6%–16.3%; Pulses: 100.0%–76.0%). The weighted-average ND-GAIN scores improved (indicating less climate vulnerability) for supply of all crops except cereals, but the weighted-average WRI score for supply deteriorated (indicating increased projected water stress) for all crops except vegetables. When just considering imports, weighted-average ND-GAIN scores deteriorated for fruits and cereals while showing no significant change for other food groups, and the WRI score deteriorated for cereals only. Conclusions Despite some notable improvements in the environmental vulnerability of The Gambia's supply of nutritionally important crops (particularly vegetables), considerable, and in some cases increasing, proportions of their supply are produced in countries that are vulnerable to climate change and future water stress. This may have implications for the availability, affordability, and hence consumption of these crops in The Gambia, ultimately exacerbating existing nutritional challenges. Exploring the options to strengthen supply resilience—such as altering trade patterns, agricultural techniques and diets—should be prioritized.